2008
DOI: 10.2139/ssrn.1260168
|View full text |Cite
|
Sign up to set email alerts
|

Better Safe than Sorry? Ex Ante and Ex Post Moral Hazard in Dynamic Insurance Data

Abstract: This paper empirically analyzes moral hazard in car insurance using a dynamic theory of an insuree's dynamic risk (ex ante moral hazard) and claim (ex post moral hazard) choices and Dutch longitudinal micro data. We use the theory to characterize the heterogeneous dynamic changes in incentives to avoid claims that are generated by the Dutch experience-rating scheme, and their effects on claim times and sizes under moral hazard. We develop tests that exploit these structural implications of moral hazard and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 33 publications
2
48
0
Order By: Relevance
“…2 States with higher insurance minimums tend to have more uninsured drivers, further accentuating the underreporting bias. 3 Support for this argument comes from Ma and Schmit (2000), who find that higher poverty rates are associated with more uninsured drivers. Second, not all states measure and report traffic collisions in the same way, making it a very unrepresentative and unbalanced panel of states.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…2 States with higher insurance minimums tend to have more uninsured drivers, further accentuating the underreporting bias. 3 Support for this argument comes from Ma and Schmit (2000), who find that higher poverty rates are associated with more uninsured drivers. Second, not all states measure and report traffic collisions in the same way, making it a very unrepresentative and unbalanced panel of states.…”
Section: Datamentioning
confidence: 99%
“…Insurance Research Council's Uninsured Motorists 2014 Edition reports that about 13 percent of drivers were uninsured in 2012, with Oklahoma topping the list with 26 percent and Massachusetts at the bottom with 4 percent. 3 Consumer Federation of America claims that most uninsured drivers have low incomes and struggle to afford the high-priced minimum liability coverage now required by all states, except for New Hampshire. 4 Pairwise correlation is 0.99 between per person and per accident medical liability and 0.63 between per person/accident medical and property liability.…”
Section: Datamentioning
confidence: 99%
“…; see also Cohen and Siegelman (2010) and sources cited therein for discussion of attempts to distinguish adverse selection from moral hazard). In recent work, Abbring, Chiappori and Zavadil (2008) review the prior literature and use advanced econometric techniques and Dutch automobile insurance data to separate these effects. They find both ex ante and ex post moral hazard effects from the unique experience rating system in Dutch automobile insurance, which contains features that facilitate the econometric separation of these effects.…”
Section: Table 2 About Herementioning
confidence: 99%
“…Until recently, the evidence for ex-ante moral hazard has quite extensively been observed in certain insurance sectors, such as car insurance (Abbring et al 2008) or work disability insurance. In the case of car insurance for example, it has been observed that taking up an insurance has led to, in certain cases, an increase in the number of claims, as insured take up more risks when driving and anticipate the insurance coverage in case of an accident (Abbring et al 2008).…”
Section: Health Insurance and Attitudes Towards Health Risks: Ex-antementioning
confidence: 99%